Mbira dzavadzimu and its space within the Shona cosmology: tracing mbira from bira to the spiritual world - Matiure, Perminus (MUZIKI, 2020)
Mbira dzavadzimu is a musical instrument commonly associated with the Zezuru, a sub-ethnic group of the Shona of Zimbabwe. Its popularity arises from its ability to ensnare the spirits in spirit mediums. It is a common belief that the Zezuru, like any other African ethnic group, have a very strong relationship with their ancestors. This progeny-progenitor relationship depicts an everlasting relationship between the living and the dead and ultimately acts as the basis of the Shona philosophy that death is not the end of life but a breakthrough into a totally new world of the invisible which they call nyikadzimu. In this article the writer will unpack the indigenous knowledge system that informs the Shona cosmology as it relates to mbira dzavadzimu and its space in Shona spirituality. The data that furnishes this article is part of the writer's unpublished Master's thesis (2009) in which he establishes the relationship between mbira dzavadzimu modes and spirit possession. The study adopted an ethnographic paradigm in which empirical data was collected through participant observation during a field study in Chikomba and Hwedza districts. The data was then analysed qualitatively and the findings revealed that both the mbira instrument and the pieces performed on it belong to the ancestors; hence there is a very strong and permanent relationship between mbira pieces and spirit possession. It is from this relationship that mbira music draws the power to evoke spirits in spirit mediums (masvikiro) during all-night ceremonies (mapira). Consequently the whole Shona cosmology greatly depends on mbira dzavadzimu.